Patent litigation as a leading market indicator. (28th August 2007) - Tang, Victor; Huang, Biao
The purpose of this paper is to introduce patent litigation as a leading indicator of market growth. We model the intensity of patent litigation and the market growth for the personal computer and cellular phone market in the USA. By means of these analytic models, we show that patent litigation is a leading indicator of market growth. We are also able very precisely to delineate discrete stages of the product's market life cycle and demarcate the time when life-cycle transitions are about to take place. We close this paper with a discussion on new lines of patent research that are potentially useful for managerial practice and for investment decisions.